Northeast India A Reader - Oinam, Bhagat; Sadokpam, Dhiren A. (Taylor & Francis, 2018)
Northeast India is a multifaceted and dynamic region that is constantly in focus because of its fragile political landscape characterized by endemic violence and conflicts. One of the first of its kind, this reader on Northeast India examines myriad aspects of the region - its people and its linguistic and cultural diversity.